2021
DOI: 10.4081/dr.2022.9188
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiome in inflammatory skin disorders: a systematic review

Abstract: The close relationship between the intestine and the skin has been widely stated, seen from gastrointestinal (GI) disorders often accompanied by skin manifestations. Exactly how the gut microbiome is related to skin inflammation and influences the pathophysiology mechanism of skin disorders are still unclear. Many studies have shown a two-way relationship between gut and skin associated with GI health and skin homeostasis and allostasis. This systematic review aimed to explore the associations between the gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 85 publications
(162 reference statements)
0
24
0
Order By: Relevance
“…As the gut microbiome has emerged as the major regulator of the gut-skin axis, recent studies on the gut microbiota and patients with inflammatory skin diseases, including AD, have been conducted [1][2][3][4][5]. The gut microbiota is a large collection of microorganisms in the human gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the gut microbiome has emerged as the major regulator of the gut-skin axis, recent studies on the gut microbiota and patients with inflammatory skin diseases, including AD, have been conducted [1][2][3][4][5]. The gut microbiota is a large collection of microorganisms in the human gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of gut microbiota diversity has been highlighted in recent studies examining the association between the gut microbiota and chronic inflammatory skin diseases, such as acne, rosacea, and psoriasis, as well as AD [3,4]. A recent systematic literature review that analyzed the association of inflammatory skin diseases with imbalance of the gut microbiota found that there were consistently significant differences in the gut microbiota between healthy individuals and patients with acne vulgaris, psoriasis, and chronic urticaria [5]. However, it was reported that studies on AD have shown conflicting results [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory bacteria such as Akkermansia muciniphila, Faecalibacterium prausnitzii, Clostridium leptum, genus Lactobacillus and Bifidobacterium have shown to protect from allergic and inflammatory diseases [ 35 ]. Anti-inflammatory bacteria might protect against CSU through the induction of Treg cells [ 76 ]. Lastly, some studies have shown the beneficial impact of probiotics in CSU patients.…”
Section: Gut Microbiome In Patients With Chronic Spontaneous Urticariamentioning
confidence: 99%
“… 9 , 10 Several studies examining differences in the composition of the intestinal microbiota between psoriasis patients and healthy controls have suggested that disorders of the intestinal microbiota may be closely related to the development of psoriasis. 11 13 Germ-free (GF) mice develop more severe psoriasis-like skin inflammation than conventional mice due to enhanced Th17 responses, indicating that the intestinal microbiota may indeed be crucial in the progression of psoriasis. 14 Moreover, sPLA2-IIA was contributed to the shaping of the gut microbiota and Pla2g2a –/– mice showed an altered intestinal microbiota which regulated the pathogenesis of psoriasis and skin carcinogenesis through co-housing experiment.…”
Section: Introductionmentioning
confidence: 99%